SISTEM PAKAR PENDIAGNOSA PENYAKIT MENULAR PADA ANJING - WITARI, KADEK RISNA; GANDHIADI, I G.K.; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 2 No 1 (2013): E-Jurnal Matematika, 2013)
The closeness of the relationship between dogs and human makes the dog can be trained, played together, lived together with human and are invited to socialize with human and other dogs. But, despite its this relationship, the dogs can also have a contagious disease that may be harmful to human. Diagnostic expert system for infectious disease in dogs for as web-based system with the media android used as a tool for diagnosing infectious diseases in dogs based on physical characteristics or symptoms that can be seen or felt without through examination of the specifics. The diagnostics final results are expected to be a reference for further examination and handling of dogs that contract the disease is detected to prevent the disease for humans. This expert system uses a forward chaining inference method and Certainty Factor to infer.
Keywords: expert systems; forward chaining; certainty factor